Ovarian adenomyoma: a case report - Weilong Liu; Tongtong Yao; Haiyan Wang; Wenjing Yu; Hongtang Shi; Jiwei Guo; Zhiqiang Liu (BMC Women's Health)
Abstract Introduction Ovarian adenomyoma is a rare gynecological tumor with a high misdiagnosis rate, leading many patients to undergo unnecessary surgeries that may affect fertility. Menstrual abdominal pain is the most common symptom, and auxiliary examinations often cannot clarify its nature. It often relies on intraoperative diagnosis, and surgical resection can achieve good therapeutic effects. Case presentation A 50-year-old woman presented with lower abdominal pain during her menstrual period for the past two months. She had a previous medical history of uterine adenomyomectomy, ovarian cystectomy, and a cesarean section. Ultrasound revealed a 5.7 × 3.8 × 4.3 cm mass on the posterior wall of the uterus, a 9.9 × 5.6 × 8.2 cm hypoechoic mass in the right posterior part of the uterus, and a 2.8 × 2.2 × 2.7 cm anechoic mass in the left ovary. CA125 (Carbohydrate antigen 125) 191.80U/ml (0–30). MRI (magnetic resonance imaging) imaging confirmed a 7.9 × 6.2 × 7.2 cm fibroid on the right posterior wall of the uterus. Consider partial degeneration of multiple uterine fibroids and benign cystic degeneration in the lower left abdomen. Surgical resection was performed smoothly, and the diagnosis was confirmed by postoperative pathology. Conclusion Ovarian adenomyoma is a rare benign gynecologic tumour with a high rate of misdiagnosis. When a patient presents with recent lower abdominal pain or dysmenorrhea, a history of endometriosis or myomectomy, and MRI findings showing irregular bleeding patterns in a pelvic mass, the possibility of extrauterine adenomyosis should be considered. Minimally invasive treatment options, such as single-port laparoscopy or vaginal dissection, may offer advantages, but caution should be exercised due to the potential for malignant tumors. Preserving fertility is something worth exploring. We hope to provide warnings to more gynaecologists and reduce misdiagnosis and unnecessary treatment.